Dom Quixote: o elogio da leitura e o sentido da religiosidade - Vianna, Marielle de Souza (2012)
This dissertation thesis has investigated the relations that have connected the meaning of reading and the sense of religiosity in Dom Quixote de La Mancha, one of the novels founders of the modern literature, by Miguel de Cervantes. The first part, beyond demonstrating that reading is a constitutive element for Cervantes work, has analyzed reading in its multiple dimensions, considering it as a social practice that has developed historically and has been effective differently in the public sphere (oral reading) and in the private one (silent reading). The second part has presented a reconstruction of Cervantes course for creating the novel, taking as reference the religiosity question. When regarding socio-historical and biographic elements, they have demonstrated how Cervantes incorporated, in his text, a critic to the ecclesial mentality and the place in which his book was written, especially discussing the problems of origin and belonging of Quixote to the only religious tradition. The third part has analyzed the relation between orality and public reading, especially concerning Cervantes figures, the cure and Sancho Pança, as representatives of the conception of the world living the oral tradition. Moreover, Sancho represents the produced knowledge, preserved and transmitted by the oral culture, and, in this tradition, religiousness has expressed genuinely; however, in the case of the cure, representative of oral reading, the religiosity is represented through an institutionalized way, since he must transmit beliefs and dogmas of the catholic doctrine. The fourth and last part has indicated how silent reading has constituted in Dom Quixote a practice which is valid for justifying the contemplative life, promoting the defense of Christian values. Thus, once silent reading provides more intimacy with the texts, it makes also possible some plurality of interpretations, and, many times, conflicting ones. Quixote interpreted his readings in a very particular means, and, in the same way, lived his religiosity. Therefore, it seems that, for Quixote, reading the novels of chivalry allowed him to find Christian virtues, as well as to exalt them, not only in his words, but also in his actions. In this investigation, it follows that, in Dom Quixote de La Mancha, the relation between religiosity and reading is reciprocally constitutive.